Evolving roles for local government in tourism development: a political economy perspective. Issue 12 (1st December 2016) - Shone, Michael C.; Simmons, David G.; Dalziel, Paul
ABSTRACT: This paper interrogates the changing role of local government in tourism development. It does so through the examination of the Hurunui District, a rural district in New Zealand which has experienced significant transformation in the tourism sector and a concomitant increase in public sector input over the past 25 years. By situating this interrogation within an evolving neoliberal public policy context, this paper explores the tensions at play between tourism stakeholders and decision-makers, and it critiques the way in which local government involvement in the sector is manifested as regulation, promotion, and ownership of key tourism resources in the District. The significance of this paper is that it extends our understanding of the role of the state in tourism and of the influence of public policy on tourism development, potentially including sustainable tourism development. Specifically, it draws our attention to the rationality, roles and activities of public sector engagement in the tourism sector, particularly at local government level. We conclude that the nature and extent of debate evident in the case study, and verified in the literature, indicates that the boundary of government activity and intervention in the tourism market is, and will continue to be, socially contested and mediated.